Double K-shell ionization of Kr induced by swift Xe54+ ions. (July 2015) - Shao, Caojie; Yu, Deyang; Wang, Wei; Xue, Yingli; Zhang, Mingwu; Yang, Bian; Song, Zhangyong; Lu, Rongchun; Liu, Junliang; Guo, Yipan; Cai, Xiaohong
Synopsis: Kα satellite and hypersatellite lines of Kr induced by 52-, 94-, 146-, and 197-MeV/u Xe 54+ ions were measured. Experimental values were compared with theoretical ones obtained within the independent electron model (IEM) employing single electron probabilities calculated with the semi-classical approach (SCA). This comparison suggests that first order perturbation approximation is consistent well with the experimental result at 197-MeV/u projectile collision while breaks down for the lower energies.